2014
DOI: 10.1038/ismej.2014.222
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community responses to a gradient of alkaline mountaintop mine drainage in Central Appalachian streams

Abstract: Microbial community composition and diversity change along chemical gradients, leading to the expectation that microbial community information might provide new gradient characterizations. Here we examine stream bacteria composition and diversity along a strong chemical gradient in Central Appalachian streams. Coal mining in the region generates alkaline mine drainage (AlkMD), causing dramatic increases in conductivity, alkalinity, sulfate and metals sufficient to degrade stream macrobiota communities througho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 57 publications
4
53
1
Order By: Relevance
“…This study employed PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) to predict functional differences in the tidal flat gradient58. The OTU table was used as the input file for metagenome imputation of individual sediment samples.…”
Section: Methodsmentioning
confidence: 99%
“…This study employed PICRUSt (Phylogenetic Investigation of Communities by Reconstruction of Unobserved States) to predict functional differences in the tidal flat gradient58. The OTU table was used as the input file for metagenome imputation of individual sediment samples.…”
Section: Methodsmentioning
confidence: 99%
“…Depressed richness of benthic macroinvertebrate communities often occurs in mining-influenced low-order streams with elevated SC (Green et al, 2000;Hartman et al, 2005;Pond et al, 2008;Cormier et al, 2013aCormier et al, , 2013bPond et al, 2014;Timpano et al, 2015). Recent studies have also found fish assemblage structure (Hitt and Chambers, 2014), salamander abundance (Wood and Williams, 2013) and richness (Muncy et al, 2014), and microbial community composition (Bier et al, 2015) to be altered in salinized mining-influenced streams; and freshwater mussel richness and densities to be depressed in salinized river segments . Water borne trace elements often occur at elevated concentrations in association with elevated salinity in such waters (Pond et al, 2008;Lindberg et al, 2011;Pond et al, 2014) and are also of concern due to potential biotic impacts (Palmer et al, 2010;Johnson et al, 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Some other studies21222324 have reported variations in bacterioplankton and archaeaplankton communities across freshwater and ocean environments, demonstrating that spatial variability was greater than seasonal patterns of variation. In addition to habitat heterogeneity25, planktonic bacterial and archaeal communities can also respond to changes in many environmental factors in water, such as salinity2627, dissolved organic matter (DOM)28, alkalinity29, temperature, and soluble reactive phosphorus (SRP)20. Moreover, temporal variation in the microbial community has been shown to be greater than spatial variation in the same habitat153031.…”
mentioning
confidence: 99%